The Debt of the Government of the Republic of Indonesia Against PT. Cipta Marga Nusaphala Persada - Zulfikar, Muh. Reza; Suprapto; Lawra, Rifqi Devi; Razy Mahka, Muh. Fachrur (State of Islamic Institute Langsa, 2023)
Early June 2023 the majority shareholder of PT. Cipta Marga Nusaphala Persada Jusuf Hamka collected a debt of 800 billion to the government. However, IBRA (National Bank Restructuring Agency) rejected CMNP's request because the company is affiliated with Bank Yama, so CMNP is not the responsibility of the Government. Therefore, CMNP filed a lawsuit with the South Jakarta District Court up to PK at (MA). In the end, in 2010 the lawsuit was won by CMNP AND the state was burdened with a 2% tax each month on the debt and it was estimated along with interest that the total was 800 billion. However, within 13 years the Government has not settled the debt. Based on this research aims to analyze the position of government debt to CMNP from the perspective of decency and justice. This research is a normative method with a normative juridical approach that uses grammatical and systematic analysis techniques. Secondary legal materials from this study consist of court decisions, related regulations, legal doctrine, and expert opinions. The results of the study show that the government's actions that have not paid off CMNP's debt are actions that violate the principles of good faith and propriety in law because one indication of implementing these principles is fulfilling the agreements made. So that the prohibition of the agreement with CMNP is an act that is inappropriate and not in good faith. In addition, these actions also violated the principle of justice because the Government did not comply with court decisions and agreements with CMNP.